51st AIAA/SAE/ASEE Joint Propulsion Conference 2015
DOI: 10.2514/6.2015-3747
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Prediction for Occurrence of Shock Train Sharp Forward Movement

Abstract: Numerical simulation was conducted using commercial CFD software FLUENT to study the influence of inner flow structures on the motion characteristics of separation oblique shock train caused by back pressure. Simulation results indicate there is a separation point of boundary layer at head of shock train. The separated flow expands in isolator and leads to movements of shock train. With shock train moving forward in isolator, the leading edge of shock train passes through the peaks and valleys of pressure alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The unstable movements of the shock train observed by Tan et al (2012) and Huang et al (2018), of which the aspect ratios satisfy the condition mentioned by Wang et al (2015), can also confirm this. Furthermore, in the investigation by Xu et al (2015), the unsteady shock train motion in the SWBLI region was presented by a 2-D numerical simulation in the absence of corner and sidewall effects. Based on the analyses above, it is reasonable to infer that the unsteady behaviour of the shock train in such case can be triggered by a 2-D interaction alone, and the 3-D effects will be ignored in the following analysis.…”
Section: Shock Train Leading Edgementioning
confidence: 99%
“…The unstable movements of the shock train observed by Tan et al (2012) and Huang et al (2018), of which the aspect ratios satisfy the condition mentioned by Wang et al (2015), can also confirm this. Furthermore, in the investigation by Xu et al (2015), the unsteady shock train motion in the SWBLI region was presented by a 2-D numerical simulation in the absence of corner and sidewall effects. Based on the analyses above, it is reasonable to infer that the unsteady behaviour of the shock train in such case can be triggered by a 2-D interaction alone, and the 3-D effects will be ignored in the following analysis.…”
Section: Shock Train Leading Edgementioning
confidence: 99%
“…Recently, various experimental and numerical investigations have been conducted to better understand the pseudo shock system. For example, Xu et al [4] reported that the effect of background waves on the growth of separation flow plays a principal role in the jump characteristic of the shock train leading edge. Li et al [5] investigated the path of shock train leading edge in complex background waves and reported a mathematical model for the path.…”
Section: Introductionmentioning
confidence: 99%
“…In Reference [14], the experiments are compared with the conventional approaches using boundary layer interaction large‐eddy simulation of a hypersonic of Mach 8 flight vehicle. In References [15] and [16], they have conducted experiments on the multiple shock wave/turbulent boundary layer interactions in a rectangular duct using Mach numbers 2.45 and 1.6. Carroll et al observed that the length of the communications and the tendency towards a repeated oblique were scaled directly with the level of confinement.…”
Section: Introductionmentioning
confidence: 99%